(36/30)x=(-35/30)

Simple and best practice solution for (36/30)x=(-35/30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (36/30)x=(-35/30) equation:


x in (-oo:+oo)

(36/30)*x = -35/30 // + -35/30

(36/30)*x-(-35/30) = 0

(36/30)*x+7/6 = 0

6/5*x+7/6 = 0 // - 7/6

6/5*x = -7/6 // : 6/5

x = -7/6/6/5

x = -35/36

x = -35/36

See similar equations:

| -14=-2w | | x-7/x-4 | | -5=-u/2 | | 278/30=14 | | 0.1x=1252/x | | 11=2(2w-2+w) | | -7x-3=6x-42 | | 12b^4-11b^2-36=0 | | 700-30x=200+20x | | 6y^2=7y-4 | | 3(x-1)+5(x-5)=5 | | 7-(2/3)x-8 | | 8b=5b | | x^2+24x+144-y^2=0 | | v=20 | | y+1.67=3.45 | | X+x+x+y+y-z+z-z= | | 50-(3x)=7x | | k-5.2+81.9=47.2 | | 21=x/3 | | -3+8(x-5)=16x+6-8x | | .5(7x-4)+3.75=4 | | X-5=-2x+22 | | u-5.11=8.91 | | 3G+5=2g+8 | | m-44=183 | | 39-12y=7-16y | | 6y+292y+30= | | 3(6y-2x)= | | m=182 | | 9c+9=45 | | 250/8 |

Equations solver categories